2015
DOI: 10.1016/j.neuron.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Alters Immunoproteostasis in APP Mice, Increasing Plaque Burden and Worsening Cognitive Behavior

Abstract: Summary Anti-inflammatory strategies are proposed to have beneficial effects in Alzheimer's disease. To explore how anti-inflammatory cytokine signaling affects Aβ pathology, we investigated the effects of adeno-associated virus (AAV2/1) mediated expression of Interleukin (IL)-10 in the brains of APP transgenic mouse models. IL-10 expression resulted in increased Aβ accumulation and impaired memory in APP mice. A focused transcriptome analysis revealed changes consistent with enhanced IL-10 signaling and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
282
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(300 citation statements)
references
References 75 publications
15
282
3
Order By: Relevance
“…However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66). However, we establish that the majority of the PGRN that accumulates at amyloid plaques is axonal.…”
Section: Discussioncontrasting
confidence: 84%
“…However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66). However, we establish that the majority of the PGRN that accumulates at amyloid plaques is axonal.…”
Section: Discussioncontrasting
confidence: 84%
“…It was only in the CC group that there was an inverse correlation between the CSF IL-10 concentrations and spontaneously reported pain intensity and discomfort (Table 3). Based on our current data, we hypothesize that IL-10 may directly modulate the painful experience by modulating the inflammatory response or by a recently identified immunoproteostasis mechanism (Chakrabarty et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
“…3K). In addition to traditional proinflammatory cytokines, two recent studies demonstrated that the antiinflammatory cytokine interleukin 10 (IL-10) negatively regulates amyloid pathology (27,28). We therefore also examined levels of IL-10 in all four groups.…”
Section: Microglial Activation and Phagocytosis Is Altered In Rag-5xfadmentioning
confidence: 99%